2004
DOI: 10.1103/physreve.69.061401
|View full text |Cite
|
Sign up to set email alerts
|

Structural crossover in dense irreversibly aggregating particulate systems

Abstract: Cluster-cluster aggregation has been simulated by off-lattice Monte Carlo methods for diffusion-limited (DLCA), ballistic-limited, and reaction-limited cluster aggregation classes. We find that as the system evolves and becomes dense, the largest cluster develops a hybrid structure with mass fractal dimension D(f) approximately 2.6 over large length scales, while at smaller length scales, the early time dilute-limit fractal structure is frozen in. The largest cluster is thus an aggregate of smaller aggregates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 39 publications
(52 reference statements)
3
35
0
1
Order By: Relevance
“…This proposition was based on simulation studies from this laboratory, which showed that DLCA can proceed creating = 1.8 fractal aggregates until the system becomes cluster dense [18]. Cluster dense is when the cluster mean nearest neighbor separation becomes comparable to the cluster size.…”
Section: Chapter 3 -Results and Discussionmentioning
confidence: 99%
“…This proposition was based on simulation studies from this laboratory, which showed that DLCA can proceed creating = 1.8 fractal aggregates until the system becomes cluster dense [18]. Cluster dense is when the cluster mean nearest neighbor separation becomes comparable to the cluster size.…”
Section: Chapter 3 -Results and Discussionmentioning
confidence: 99%
“…Subsequently our laboratory has reported gelation of soot in laminar diffusion flames (Sorensen et al 1998;Kim et al 2006). Simulations (Gimel et al 1995(Gimel et al , 1999Hasmy and Jullien 1996;Fry et al 2004) imply that any system of particles undergoing aggregation can form a gel if the combining particles do not coalesce, and if the time to reach the gel point is shorter than other time scales that can deter gel formation. Non-coalescence is necessary so that the aggregating particles will form a non-dense (ramified) fractal aggregate with fractal dimension, D, less than the spatial dimension, d. When D < d, the average cluster separation to cluster size ratio falls with time during aggregation until the separation equals the size.…”
Section: Aerosol Gelationmentioning
confidence: 99%
“…In MD, the solute−solute, solute−solvent, and solvent−solvent interactions are described by a truncated Lennard-Jones (12-6) potential: (2) where σ is the particle diameter, r ij is the separation between centers of particles i and j, r cut is the cutoff distance chosen to be 2.5σ, and ε αβ is the potential well-depth between α and β particles (α,β = A,B). The dimensionless potential well depth is defined as (3) where T ref is the reference temperature chosen to be 121 K in these simulations. The reference temperature and particle size (σ = 3.4A) were chosen on the basis of the Lennard-Jones model for liquid argon.…”
Section: Methodsmentioning
confidence: 99%